Anisotropic MOF / MoS2 nanoparticle electrorheological fluid and preparation method thereof
The anisotropic MOF/MoS2 nanoparticles prepared by hydrothermal method and solvent thermal method solve the problem of insufficient anti-settlement performance of the current-changing liquid under high electric field strength, achieve higher anti-settlement and interface polarization capabilities, and improve the shear strength and current-changing efficiency of the current-changing liquid.
Patent Information
- Application Number
- CN202411741824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The existing current-changing liquid has insufficient anti-settlement performance under high electric field strength, resulting in rapid agglomeration or phase separation of the dispersed phase, affecting the stability and performance of the current-changing liquid.
Anisotropic MOF/MoS2 nanoparticles were prepared by a combination of hydrothermal method and solvothermal method. The unique layered flake structure of MoS2 improved conductivity and interface polarization ability, and reduced ion doping to avoid disturbances of crystal defects and impurity ions.
The anti-settlement performance and interface polarization capability of the current-changing liquid are improved, the shear strength and current-changing efficiency are enhanced, and the stability and high performance of the current-changing liquid are ensured.
Smart Images

Figure CN119552699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrorheological fluid material and a preparation method thereof, and in particular to an anisotropic MOF / MoS 2 Nanoparticle electrorheological fluid and preparation method thereof. Background Art
[0002] At present, smart materials are at the forefront of the development of modern new materials and have broad application prospects in the field of scientific research. Electrorheological fluid is defined as a smart material. It has the advantages of rapid reversible phase change from liquid to solid under the action of electric field, fast response speed, low energy consumption, etc., so it has considerable research value. At present, the intelligent advantages of electrorheological fluid such as rapidity, reversibility, and precise control make it irreplaceable in the fields of aerospace, smart cars, defense industry, and biomedicine.
[0003] Electrorheological fluid is a suspension system composed of a dispersed phase and a dispersion medium. When an external electric field is applied to cause the voltage to rise sharply in a short period of time, the electrorheological particles become polarized, the particles attract each other, migrate across the gap between parallel electrodes, and form a chain or columnar structure along the direction of the electric field, thereby exhibiting solid-like properties such as shear resistance.
[0004] Metal organic framework materials MOFs have the advantages of low density, large specific surface area, high porosity, etc. When used as dispersed phase, they can significantly improve the interfacial polarization effect and improve the anti-sedimentation performance of electrorheological fluids. The stronger the anti-sedimentation ability, the smaller the probability of rapid agglomeration or phase separation of the dispersed phase in a short period of time, the less pure dispersion medium is separated, and the more stable the electrorheological system. In order to improve the performance of electrorheological fluids, one nanomaterial can be attached to the surface of another nanomaterial, and the advantages of both materials can be used at the same time, which sometimes produces an effect where one plus one is greater than two.
[0005] Comparison CN118344921A-A square anisotropic chromium ion doped MOF / SiO 2 Composite material electrorheological fluid and preparation method thereof, the present invention mainly adopts MoS 2 Replace SiO 2 , MoS 2 The lamellar structure will bring good conductivity to the material, which is more conducive to the rapid accumulation of charges on the surface of the material, thereby improving the interface polarization ability and anti-sedimentation ability. If ions are doped in the material, after doping, the energy level of the impurity atoms will interact with the energy band in the crystal to form a new energy band structure, resulting in a decrease in particle conductivity. In addition, doping will also cause crystal defects and disturbances of impurity ions, so that the movement of ions in the crystal is hindered, thereby reducing conductivity. Therefore, the present invention does not introduce additional ions for doping.
[0006] Comparison with CN117467184A - a MoS 2 Based aerogel and its preparation method and application, the present invention mainly utilizes MoS 2 The unique layered structure of the metal organic framework / MoS was prepared by hydrothermal and solvothermal methods. 2 The composite material is made of MoS and is mixed with dimethyl silicone oil in a certain ratio (10wt%) to form an electrorheological fluid. 2 There are obvious differences between the two.
[0007] Object and content of the invention
[0008] The purpose of the present invention is to provide a MOF and MoS 2 Hybrid nanoparticle electrorheological fluid, whose dispersed phase is an anisotropic MOF / MoS 2 Nanoparticles, the continuous phase is dimethicone.
[0009] The present invention also aims to provide a method for preparing MOF / MoS by combining a hydrothermal method and a solvothermal method. 2 Nanoparticle method, preparation of MOF / MoS by two-step method 2 Nanoparticles were first prepared by hydrothermal method to prepare MoS2 nanoparticles, and then MOF / MoS was prepared by solvothermal method. 2 Nanoparticles. The high porosity of MOFs can not only improve the sedimentation resistance of MOFs, but also enhance the surface polarization of MOFs. Since the hybrid material has a large specific surface area, it has a higher surface activity, thereby enhancing its electrorheological properties. The present invention has the characteristics of simple preparation process, cheap raw materials, good safety, and no special requirements for test equipment.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] The electrorheological fluid prepared by the present invention has a dispersed phase that exhibits anisotropic MOF / MoS 2 Nanoparticles, the continuous phase is dimethicone.
[0012] The preparation process of the electrorheological fluid comprises the following steps:
[0013] (1) 3.829 g of thiourea, 3.032 g of hexaammonium heptamolybdate tetrahydrate and 1.5 g of sodium dodecyl sulfate were added to 85 mL of deionized water and stirred for 1 h. The resulting solution was transferred to a hydrothermal kettle and heated hydrothermally at 220 °C for 24 h. After cooling to room temperature, the resulting suspension was washed with deionized water and anhydrous ethanol and centrifuged to obtain MoS 2 Nanoparticles were dried at 75 °C for 12 h to obtain MoS 2 Solid powder.
[0014] (2) Add 65 mL of dimethylformamide and 10 mL of anhydrous methanol into a 100 mL beaker to obtain a mixed solution. Then weigh 3.5 g of terephthalic acid, 0.7 g of hexadecyltrimethylammonium bromide and 0.02 g of molybdenum disulfide and add them to the mixed solution, and stir at room temperature until they are completely dissolved.
[0015] (3) Add 3.5 mL of acetic acid to the above solution and stir for 10 min, then add 2 mL of tetrabutyl titanate and stir for 30 min, and heat at 150 °C by solvothermal method for 24 h.
[0016] (4) After cooling to room temperature, the obtained suspension was washed with dimethylformamide and centrifuged twice, washed with anhydrous methanol twice, and washed with anhydrous ethanol once to obtain MOF / MoS 2 The nanoparticles were dried at 75 °C for 12 h to obtain solid powder.
[0017] (5) The dried sample and dimethyl silicone oil are mixed in a certain ratio (10 wt%) to form an electrorheological fluid.
[0018] Compared with the prior art, the present invention has the following significant advantages:
[0019] 1. The preparation method of the present invention adopts hydrothermal method and solvothermal method to prepare MOF / MoS in two steps 2 Nanoparticles. The preparation process is simple and easy to operate, the raw materials are easily available, and the components and properties are easy to control. The obtained samples are approximately square and anisotropic, with a size of about several hundred nanometers.
[0020] 2. The electrorheological fluid prepared by this material and dimethyl silicone oil has high shear strength. 2 The excellent conductivity brought by the unique layered structure composed of sulfur atoms and molybdenum atoms is conducive to the rapid migration of charges, thereby promoting the rapid accumulation of charges on the surface of the material, making the composite material produce stronger interfacial polarization, and using MOFs to improve the interfacial polarization ability and anti-sedimentation ability, making the prepared MOF / MoS 2 Nanoparticles have good comprehensive properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 SEM image of MOF prepared by solvothermal method
[0022] Figure 2 Preparation of MoS by hydrothermal method 2 Transmission electron micrograph of
[0023] Figure 3 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.02g2 -0.02 shear strength and shear rate relationship diagram
[0024] Figure 4 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.02g 2 -0.02 SEM image
[0025] Figure 5 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.02g 2 -0.02 TEM image
[0026] Figure 6 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.03g 2 -0.03 shear strength and shear rate relationship diagram
[0027] Figure 7 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.03g 2 -0.03 SEM image
[0028] Figure 8 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.04g 2 -0.04 shear strength and shear rate relationship diagram
[0029] Fig. 9 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 SEM image of hybrid material when the addition amount is 0.04g
[0030] Fig.10 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Transmission electron microscopy image of the hybrid material when the addition amount is 0.04g
[0031] Fig.11 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 XRD pattern of hybrid material when the addition amount is 0.02g DETAILED DESCRIPTION
[0032] Example 1 (Preparation of MOF Nanoparticles by Solvothermal Method)
[0033] 3.5g terephthalic acid and 0.7g hexadecyltrimethylammonium bromide were dispersed in a mixed solution of 65mL N,N-dimethylformamide and 10mL anhydrous methanol, stirred until completely dissolved, and then 3.5mL acetic acid was added. Stirring was continued for 10min, and then 2mL tetrabutyl titanate was added and stirred thoroughly. Solvothermal reaction was carried out at 150℃ for 24h. The scanning electron microscopy of the prepared MOF sample is as follows Figure 1 As shown, the scanning photos show that the obtained nanoparticles have uniform morphology, are all cubic blocks, and have a size of about several hundred nanometers.
[0034] Example 2 (MoS 2 When the addition amount is 0.02g, MOF / MoS 2 Hybrid Materials
[0035] 3.829 g thiourea, 3.032 g hexaammonium heptamolybdate tetrahydrate and 1.5 g sodium dodecyl sulfate were added to 85 mL deionized water and stirred for 1 h. The resulting solution was transferred to a hydrothermal kettle and heated at 220 °C for 24 h. After cooling to room temperature, the resulting suspension was washed with deionized water and anhydrous ethanol and centrifuged to obtain MoS 2 Nanoparticles were dried at 75 °C for 12 h to obtain MoS 2 Solid powder.
[0036] 3.5 g terephthalic acid, 0.7 g hexadecyltrimethylammonium bromide and 0.02 g MoS 2 Disperse into a mixed solution of 65 mL N,N-dimethylformamide and 10 mL anhydrous methanol, stir until completely dissolved, add 3.5 mL acetic acid, continue stirring for 10 min, add 2 mL tetrabutyl titanate and stir well, and react at 150 ° C for 24 h. 2 Transmission electron microscopy Figure 2 As shown, it presents a layered structure. 2 Sample scanning and transmission electron microscopy Figure 4 , 5 As shown in the figure, the scanning photo shows that there are nano-layered particles attached to the surface of the cube, and the transmission photo shows that the cube is a solid structure with a layered structure similar to petals attached to the surface, and some MoS 2 The presence of MOFs proves that it is not a simple surface adsorption. 2 Participated in the growth of MOF matrix and achieved hybridization with MOF structure. The XRD pattern of the prepared sample is shown in Fig.11 As shown, MoS appears at 2θ = 14.9 and 33.88 2The characteristic diffraction peaks correspond to the (002) and (110) crystal planes. The diffraction peaks are sharp and the crystallinity is good. The corresponding PDF card number is 74-0932. By comparing the diffraction peaks in the spectrum with the standard PDF card, it can be determined that the hybrid contains MoS 2 .
[0037] At room temperature, take 0.15g MOF / MoS 2 After grinding with 1.5 mL of dimethyl silicone oil, the mixed liquid was added to the electrorheological tester. By changing the electric field intensity, several sets of shear stress and shear rate curves under different voltages were obtained, such as Figure 3 As shown. The electrorheological fluid exhibits Newtonian fluid characteristics in its initial state, and the shear strength increases linearly with the shear rate. When an external electric field is applied, the electrorheological fluid becomes a non-Newtonian fluid, and the particles polarize rapidly in the electric field, and the dipoles attract each other. As the electric field strength increases, the shear stress also increases, and then a platform area appears, which is determined by the electrorheological efficiency η=(τ E -τ 0 / τ 0 ) calculation formula shows that the electrorheological efficiency is 165, showing good electrorheological performance.
[0038] Example 3 (MoS 2 When the addition amount is 0.03g, MOF / MoS 2 Hybrid Materials
[0039] 3.829 g thiourea, 3.032 g hexaammonium heptamolybdate tetrahydrate and 1.5 g sodium dodecyl sulfate were added to 85 mL deionized water and stirred for 1 h. The resulting solution was transferred to a hydrothermal kettle and heated at 220 °C for 24 h. After cooling to room temperature, the resulting suspension was washed with deionized water and anhydrous ethanol and centrifuged to obtain MoS 2 Nanoparticles were dried at 75 °C for 12 h to obtain MoS 2 Solid powder.
[0040] 3.5 g terephthalic acid, 0.7 g hexadecyltrimethylammonium bromide and 0.03 g MoS 2 Disperse into a mixed solution of 65 mL N, N-dimethylformamide and 10 mL anhydrous methanol, stir until completely dissolved, add 3.5 mL acetic acid, continue stirring for 10 min, then add 2 mL tetrabutyl titanate and stir thoroughly, and perform solvent thermal reaction at 150 °C for 24 h.
[0041] At room temperature, take 0.15g MOF / MoS 2 After grinding with 1.5 mL of dimethyl silicone oil, the mixed liquid was added to the electrorheological tester. By changing the electric field intensity, several sets of shear stress and shear rate curves under different voltages were obtained, such as Figure 6As shown, the electrorheological efficiency is 352, showing good electrorheological performance.
[0042] Figure 7 MoS prepared by solvothermal treatment at 150 °C for 24 h 2 Hybrid material MOF / MoS when the addition amount is 0.03g 2 -0.03 scanning electron microscope image, the morphology shows that the nanoparticles are attached to the surface of the cube.
[0043] Example 4 (MoS 2 When the addition amount is 0.04g, MOF / MoS 2 Hybrid Materials
[0044] 3.829 g thiourea, 3.032 g hexaammonium heptamolybdate tetrahydrate and 1.5 g sodium dodecyl sulfate were added to 85 mL deionized water and stirred for 1 h. The resulting solution was transferred to a hydrothermal kettle and heated at 220 °C for 24 h. After cooling to room temperature, the resulting suspension was washed with deionized water and anhydrous ethanol and centrifuged to obtain MoS 2 Nanoparticles were dried at 75 °C for 12 h to obtain MoS 2 Solid powder.
[0045] 3.5 g terephthalic acid, 0.7 g hexadecyltrimethylammonium bromide and 0.04 g MoS 2 Disperse into a mixed solution of 65 mL N, N-dimethylformamide and 10 mL anhydrous methanol, stir until completely dissolved, add 3.5 mL acetic acid, continue stirring for 10 min, then add 2 mL tetrabutyl titanate and stir thoroughly, and perform solvent thermal reaction at 150 °C for 24 h.
[0046] At room temperature, take 0.15gMOF / MoS 2 After grinding with 1.5 mL of dimethyl silicone oil, the mixed liquid was added to the electrorheological tester. By changing the electric field intensity, several sets of shear stress and shear rate curves under different voltages were obtained, such as Figure 8 As shown, the electrorheological efficiency is 103, showing good electrorheological performance.
[0047] Fig. 9 Scanning electron microscope image of the hybrid material prepared by solvothermal treatment at 150°C for 24 hours with a MoS2 addition of 0.04 g; it can be seen that nanoparticles are attached to the surface of the cube. Fig.10 Transmission electron microscopy image of the hybrid material prepared by solvothermal treatment at 150℃ for 24h with a MoS2 addition of 0.04g; the morphology is characterized by nano-layered particles attached to the surface of the solid cube, and the layers are similar to petals, which is consistent with the MoS 2 characteristics.
Claims
1. A MOF / MoS2 nanoparticle electrorheological fluid material, characterized in that: The dispersed phase of the material is an anisotropic MOF / MoS2 nanoparticle, and the continuous phase is dimethyl silicone oil; The dispersed phase of the electrorheological fluid is prepared by hydrothermal and solvothermal methods. The material has a unique morphology and is a nearly square surface-attached lamellar structure. The electrorheological fluid formulated with dimethyl silicone oil has good anti-sedimentation properties, a small density, and an electrorheological efficiency of 352, showing a good electrorheological effect.
2. The anisotropic MOF / MoS2 nanoparticle electrorheological material according to claim 1, characterized in that: The preparation process of the electrorheological fluid comprises the following steps: (1) 3.829 g of thiourea, 3.032 g of hexaammonium heptamolybdate tetrahydrate and 1.5 g of sodium dodecyl sulfate were added to 85 mL of deionized water and stirred for 1 h; heated at 220 ° C for 24 h by hydrothermal method; after cooling to room temperature, the obtained suspension was washed with deionized water and anhydrous ethanol and centrifuged to obtain MoS2 nanoparticles, and dried at 75 ° C for 12 h to obtain solid powder; (2) Add 65 mL of dimethylformamide and 10 mL of anhydrous methanol into a 100 mL beaker to obtain a mixed solution; then weigh 3.5 g of terephthalic acid, 0.7 g of hexadecyltrimethylammonium bromide and molybdenum disulfide and add them to the mixed solution, and stir at room temperature until they are completely dissolved; (3) Add 3.5 mL of acetic acid to the above solution and stir for 10 min, then add 2 mL of tetrabutyl titanate and stir for 30 min, and heat at 150 ° C by solvothermal method for 24 h; (4) After cooling to room temperature, the obtained suspension was washed with dimethylformamide and centrifuged twice, washed with anhydrous methanol twice, and washed with anhydrous ethanol once to obtain MOF / MoS2 nanoparticles, which were dried at 75°C for 12 h to obtain solid powder; (5) The dried sample and dimethyl silicone oil are mixed at a ratio of 10 wt % to form an electrorheological fluid.
Citation Information
Patent Citations
MoS2-based aerogel as well as preparation method and application thereof
CN117467184A
Square anisotropic chromium ion doped MOF / SiO2 coated composite material electrorheological fluid and preparation method thereof
CN118344921A